ADVERSE DRUG REACTIONS AND POLY-PHARMACY IN GERIATRIC PATIENTS: A PHARMACOVIGILANCE BASED OBSERVATIONAL STUDY - Dr. P. C. Vasantha Rao (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Geriatric patients are particularly susceptible to adverse drug reactions (ADRs) due to age-related physiological changes, multiple co-morbidities, and the prevalent practice of poly-pharmacy. In India, the prevalence of poly-pharmacy among older adults is significant, raising concerns about medication safety in this population. Aims and Objectives: To evaluate the incidence, patterns, and risk factors associated with ADRs among geriatric patients, with a specific focus on the impact of poly-pharmacy, within an Indian tertiary care hospital setting.Materials: A prospective observational study was conducted over six months in the general medicine department of a tertiary care teaching hospital in India. Geriatric patients (aged ≥60 years) admitted during the study period were enrolled. Data collected included demographic details, medical history, comprehensive drug prescriptions, and documented ADRs. ADRs were assessed for causality using the World Health Organization-Uppsala Monitoring Centre (WHO-UMC) criteria, severity using the Hartwig and Siegel scale, and preventability using the Schumock and Thornton criteria. Polypharmacy was defined as the concurrent use of five or more medications. Statistical analyses were performed to identify associations between polypharmacy and the occurrence of ADRs.Results: Among the 450 geriatric patients studied, 135 (30%) experienced at least one ADR. The most commonly affected organ systems were gastrointestinal (35%), central nervous system (25%), and cardiovascular (20%). Polypharmacy was observed in 70% of patients and was significantly associated with the occurrence of ADRs (p